Platelet Aggregation in Whole Blood: The Role of Thromboxane A2 and Adenosine Diphosphate - Carter, A J; Heptinstall, S (Thrombosis and Haemostasis, 1985)
The platelet aggregation that occurred in whole blood in response to several aggregating agents (collagen, arachidonic acid, adenosine diphosphate, adrenaline and thrombin) was measured using an Ultra-Flo 100 Whole Blood Platelet Counter. The amounts of thromboxane B2 produced were measured by radioimmunoassay. The effects of various inhibitors of thromboxane synthesis and the effects of apyrase, an enzyme that destroys adenosine diphosphate, were determined.Platelet aggregation was always accompanied by the production of thromboxane B2, and the amounts produced depended on the nature and concentration of the aggregating agent used. The various inhibitors of thromboxane synthesis - aspirin and flurbiprofen (cyclo-oxygenase inhibitors), BW755C (a cyclo-oxygenase and lipoxygenase inhibitor) and dazoxiben (a selective thromboxane synthase inhibitor) - did not markedly inhibit aggregation. Results obtained using apyrase showed that adenosine diphosphate contributed to the aggregation process, and that its role must be acknowledged when devising means of inhibiting platelet aggregation in vivo.
Keywords: Platelet aggregation; Thromboxane A2; ADP